Microbiological drinking water quality in educational centers and health establishments in Costa Rica 2023 - Rivera-Navarro, Pablo César (2024)
The results the microbiological quality of water for human use and consumption in educational centers in Costa Rica are presented, in addition to the entrance and interior networks of health establishments, through sampling carried out on the water supplied by the official operating entities (AyA, Municipalities-ESPH and communal aqueducts or ASADAS), during the year 2023. For educational centers, fecal indicators and the concentration of free residual chlorine were monitored, while for health establishments the count of heterotrophic bacteria and Pseudomonas aeruginosa were also considered. The results indicate that in educational centers 1038 samples were collected in 671 educational centers, to identify that 97 % received drinking quality water and 3 % presented signs of fecal contamination. In 88 health establishments, 287 samples were collected, to show that 98 % are free of fecal contamination at the entrance, while 100 % did not present fecal indicators in their internal network; however, Pseudomonas aeruginosa was detected in 9 % in the water inlets and 14 % in the internal network. On the other hand, in the water inlet samples from health centers, 94 % presented determinations with residual chlorine in accordance with the Regulation for the Quality of Drinking Water, while in internal networks only 64% met this require.